Socio-Hydrological Flood Risk Communication and Community Preparedness in Ancar Riverbank, Mataram - Janati, Janati; Hadi, Agus Purbathin; Muhajira, Muhajira (Jurnal Biologi Tropis, 2026)
Urban flooding is a hydrometeorological threat that is influenced by the interaction between river systems, spatial planning, rainfall, and community social readiness. This study aims to analyze the relationship between the communication strategy of disaster information management and community preparedness in dealing with floods on the banks of the Ancar River, Mataram City. The study used a quantitative approach with a cross-sectional associative survey design on 43 respondents selected through multistage stratified random sampling; data were collected using Likert scale questionnaires, documentation, limited observations, and supporting interviews, then analyzed descriptively and correlated Spearman Rank. The results showed that communication strategies were in the low category (average 2.47), while community preparedness was in the medium category (average 2.65). There was a positive and significant relationship between communication strategies and community preparedness (rs = 0.509; p < 0.001). These findings conclude that the quality of messages, access to information, and community participation are more determinants of preparedness than one-way information dissemination. Implication, disaster information managers need to strengthen community-based risk communication, local early warning, and disaster education that is integrated with the management of urban socio-hydrological systems.